Admiral Nimitz the commander of the Pacific Ocean theater - Harris, Brayton (Palgrave Macmillan, 2011)
A portrait of a World War II admiral traces his pivotal role in commanding all U.S. and Allied air, land, and sea forces in the Pacific after the attack on Pearl Harbor.